Agriculture House Dengan Penekanan Permaculture Di Pekanbaru - S, Mira D; H, Stevan; A, Ratna (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Currently humans are exposed to future unclear with looming crises , such as the energy crisis , social crisis , the food crisis and many other crises that might befall human life in the near future . Before the days of modern society manages natural resource that describes an ongoing (Sustainablity) . Permaculture offers techniques and ideas that help us towards the environment , culture , and a healthy society . Therefore , an idea arose to design a facility that can accommodate the Agriculture Training activities for the community to determine the manner and form and space patterns with a mass order Permaculture approach to the concept of Green Architecture. That uses energy-efficient management of healthy plants with hydroponics and agricultural way of open , to facilitate the activities of the education and training of Pekanbaru Agriculture House . In terms of architectural , Permaculture approach applied to the processing site, the arrangement of masses , and the pattern of spatial relations . as a means to help the farming process.Keywords : Agriculture House Pekanbaru , Permaculture , Green Architecture.